One-Week Self-Guided Internet Cognitive Behavioral Treatments for Insomnia in Adults With Situational Insomnia During the COVID-19 Outbreak - Zhang, Chenxi; Yang, Lulu; Liu, Shuai; Xu, Yan; Zheng, Huirong; Zhang, Bin (Frontiers in Neuroscience, 2021)
Objective: In the current global home confinement due to COVID-19, most individuals are facing unprecedented stress which can induce situational insomnia. We explored the efficacy of self-guided online Cognitive Behavioral Treatment for Insomnia (CBTI) on situational insomnia during COVID-19. Methods: Participants were recruited from March to April in 2020 in Guangzhou, China. A one-week Internet CBTI intervention was performed for all individuals with situational insomnia. Pre-Sleep Arousal Scale (PSAS), Insomnia Severity Index (ISI) and Hospital Anxiety and Depression Scale (HADS) were measured before and after the intervention and compared between individuals who completed and those who didn’t. Results: One-hundred and ninety four patients with situational insomnia were included. For PSAS score, significant group effects were found on total score (p = 0.003), somatic score (p = 0.014) and cognitive score (p = 0.009). Time effect was significant on total score (p = 0.004) and cognitive score (p < 0.001). There was a significant group × time effect of the somatic score (p = 0.025). For ISI total score, there were significant time effect (p < 0.001) and group × time effect (p = 0.024). For the HAD score, a significant group effect was found on the anxiety score (p = 0.045). The HAD scales were all found significant time effects for the total score, anxiety, and depressive symptoms (all p < 0.001). Conclusion: Our study suggests well efficacy of CBTI on situational insomnia during COVID-19 for adults in the community, as well as on pre-sleep somatic hyperarousal symptom.